THE INFLUENCE OF WORD CHAIN GAME ON INCREASING THE EIGHTH GRADE STUDENTS’ VOCABULARY AT MTS BARANA JENEPONTO - Ramadani, Wahyuni; Naro, Wahyuddin; Nur, Nur Aliyah (English Language Teaching for EFL Learners Journal, 2020)
The research aims at finding out the influence of Word Chain Game in increasing the students’ vocabulary with two research objectives.This research was conducted at MTs Barana Jeneponto Regency in Academic Year 2018/2019. In this research, the population was 60 students in the eighth grade. The sample was 40 students. There were 20 students in Class VIII A as experimental class and 20 students in VIII B as controlled class. The research applied non equivalent control grup design. The instrument used to collect the data was writing test, in fill in the blank form. The result of the data analysis indicated that there was a significant improvement in the students’ vocabulary after being taught using Word Chain Game. It was proved by the result of the statistical analysis of the level significance P = 0.05 with degree of freedom (df) = 38 indicated that the t-test values of the students’ vocabulary (2.492) was higher than t-table value (2.042). Therefore, word chain game also gives opportunities for the development of teachers, learners, and learning itself. Those opportunities can increase students’ motivation and responsibility, a student-centered approach based on individualization, and also accepting the new and dynamic learner's and teacher's roles.